Decrease anxiety in the third trimester of pregnancy: impact on hypnobirthing - Lutfiana Puspita Sari; Rosalinna Rosalinna (Jurnal Kesehatan Ibu dan Anak, 2021)
Most pregnant women experience worries, anxieties, and fears both during pregnancy, during labor, and after delivery. Relaxation-hypnobirthing is one of the non-pharmacological therapies that can be done to overcome psychological problems that often occur in the third trimester of pregnancy. This study aims to analyze the effect of hypnobirthing relaxation therapy on anxiety experienced by pregnant women in the third trimester of pregnancy. This study used a pre-experimental design with a pretest-post-group design. It used purposive sampling with 60 third-trimester of pregnant women as respondents. The data normality test uses the skewness value and the standard error results from 2 so that the data distribution is normal. Test data analysis using Paired T-Test. Based on the characteristics of most respondents aged 20-35 years old as many as 40 people (66.67%), most respondents with junior high school-high school education as many as 30 people (50%), the majority of respondents being housewives as many as 34 people (56.7%) and for parity the majority of primiparas as many as 42 people (70%). Bivariate analysis showed that the p-value of anxiety is 0.000 with the difference of mean is 7.41. There is an effect of hypnobirthing relaxation on reducing anxiety in third-trimester pregnant women.